1998
DOI: 10.1152/jn.1998.79.2.964
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Stimulation of the Intracranial Dura Induces Enhanced Responses to Facial Stimulation in Brain Stem Trigeminal Neurons

Abstract: Chemical activation and sensitization of trigeminal primary afferent neurons innervating the intracranial meninges have been postulated as possible causes of certain headaches. This sensitization, however, cannot explain the extracranial hypersensitivity that often accompanies headache. The goal of this study was to test the hypothesis that chemical activation and sensitization of meningeal sensory neurons can lead to activation and sensitization of central trigeminal neurons that receive convergent input from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
558
1
4

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 549 publications
(598 citation statements)
references
References 82 publications
24
558
1
4
Order By: Relevance
“…[15][16][17][18] Recently, the R2 component of the nBR was examined before and after unilateral GON blocks where it was found that the R2 latency increased and area under the curve (AUC) decreased after GON blockade. 13,14 This result provides empirical evidence for a functional influence on trigeminal nociceptive inputs from cervical afferents. Conceivably, occipital activation of the TCN represents the cervicogenic equivalent to application of an "inflammatory soup" onto the dura that has been shown to induce central sensitization and ensuing increased sensitivity to trigeminal inputs.…”
mentioning
confidence: 64%
See 1 more Smart Citation
“…[15][16][17][18] Recently, the R2 component of the nBR was examined before and after unilateral GON blocks where it was found that the R2 latency increased and area under the curve (AUC) decreased after GON blockade. 13,14 This result provides empirical evidence for a functional influence on trigeminal nociceptive inputs from cervical afferents. Conceivably, occipital activation of the TCN represents the cervicogenic equivalent to application of an "inflammatory soup" onto the dura that has been shown to induce central sensitization and ensuing increased sensitivity to trigeminal inputs.…”
mentioning
confidence: 64%
“…12 Further support was provided by modulation of the nociceptive blink reflex (nBR) following blockade of the GON. 13,14 The nBR is a trigeminofacial brainstem reflex and has been established as a valid technique for assessing central trigeminal transmission. [15][16][17][18] Recently, the R2 component of the nBR was examined before and after unilateral GON blocks where it was found that the R2 latency increased and area under the curve (AUC) decreased after GON blockade.…”
mentioning
confidence: 99%
“…A platinum-coated tungsten microelectrode (impedance 4-6 MΩ) was lowered repeatedly into the medullary dorsal horn in search for a target unit. At the end of the experiment, a small lesion was produced at the recording site and its localization in the dorsal horn was determined postmortem using histological analysis as described before (Burstein et al, 1998). Single-unit activity in the trigeminal ganglion (group 3) was recorded using a platinum-coated tungsten microelectrode (impedance 500 KΩ) lowered through a 2-mm circular opening that was drilled in the left parietal bone, about 2 mm caudal to the Bregma suture and 2 mm left to the midline.…”
Section: Experiments Procedures Surgical Preparationmentioning
confidence: 99%
“…A neuron was identified as a meningeal nociceptor if it responded with a constant latency to electrical stimuli from the dura but not to noxious mechanical stimuli from adjacent structures (i.e., pericranial muscles, cornea, vibrissae and ophthalmic skin). Conduction velocity was calculated using the shortest response latency to electrical stimulation of the dura which was divided by 12.5 mm -the distance between the trigeminal ganglion and the stimulation site in the dura (Burstein et al, 1998). Based on conduction velocity, neurons were classified a C-units (≀1.5 m/sec) or AÎŽ-units (>1.5 m/sec).…”
Section: Meningeal Nociceptorsmentioning
confidence: 99%
“…During a migraine attack these central sensory neurons may become sensitized, ('central sensitization') resulting in further pain progression. 12 This hypothesized pathophysiologic mechanism is a valid rationale for the early treatment of migraine pain.…”
mentioning
confidence: 99%